FAQR: LA YAMLIKU SYAI'AN WALA YAMLIKU SYAI'UN - Fuady, Muhammad Noor (Pascasarjana UIN ANTASARI Banjarmasin, 2007)
Sutr tuki.s in thc vieu̇ hrs r vc h'gl' d.grcc conrl)rrcd r;rh ri.h rroplc. l)coflc who ar. poor or dcsrih,te h thc Sulirics Liier will ger i high dcgrcc,l thc dcsirure verc willing ard pleisrd with ihc sitrGtion thir hiptcncLl ro hlm. Iiven ldter indigenr persn vill fi61 go ro hcaletr than dch l,coplc. l.digcdr person rvho g:raal rn,t sirccflty willgct rhc r..w,r(|. {4,ilc rhe grcedr o!ed d not gc hr rcward of rhar pov.rr! lixplanrcd rh^l ;,di8cnr pcol)lc irc trr,.nr !r l sii roserhd rnd.l)s.r i, (lxl onJudsc.rcor I)ay.",